2013
DOI: 10.1007/s11665-013-0825-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansion, Electrical Resistivity, and Spreading Area of Sn-Zn-In Alloys

Abstract: Thermal expansion and electrical resistivity of alloys based on Sn-Zn eutectic with 0.5, 1.0, 1.5, and 4.0 wt.% additions of In were studied. Thermal expansion measurements were performed using thermomechanical analysis tester over 223-373 K temperature range. Electrical resistivity measurements were performed with four-probe method over 298-423 K temperature range. The electrical resistivity of alloys increases linearly with temperature and concentration of In; also coefficient of thermal expansion of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
3
17
0
1
Order By: Relevance
“…For the alloys in the present study, the wetting angle seems to be practically independent of wetting time. Similarly, we earlier [15] observed, with the use of the same flux as in this study, that the spreading area does not increase over time. Figure 1(a), based on the example of an alloy containing 1.5% of In, illustrates that the spreading area increases with increasing temperature…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…For the alloys in the present study, the wetting angle seems to be practically independent of wetting time. Similarly, we earlier [15] observed, with the use of the same flux as in this study, that the spreading area does not increase over time. Figure 1(a), based on the example of an alloy containing 1.5% of In, illustrates that the spreading area increases with increasing temperature…”
Section: Resultssupporting
confidence: 90%
“…For longer wetting times, the thickness of the -Cu 5 Zn 8 phase continues to increase, while -CuZn 4 in the case of Sn-Zn/Cu couples begins to disappear and grows very little in the case of Sn-Zn-1.5% In/Cu couples. Moreover, just 0.5% of In is sufficient to keep the -CuZn 4 stable even after 60 min of wetting (Figures 6 and 7), as we observed earlier [15]. The bright spots between the -CuZn 4 and -Cu 5 Zn 8 in Figure 6 are, according to EDS analysis, composed mostly of Sn with In content somewhat higher than the In content in the Sn-Zn-In solder.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Kang et al [12] observed a similar effect of increased electrical resistivity with the addition of Cu in alloys. The Zn-Al-Cu solder exhibited an electrical resistivity of 5.5 to 7.0 lX cm at room temperature, which was lower than that of the Sn-37Pb solder (14.25 lX cm [18] ). The obtained electrical resistivity and CTE for ZnAl with Cu are similar to those for ZnAl with Ag, [6] which were 24.03, 25.27, and 29.75 cm 3 /mol for 0.5, 1.0, and 1.5 pct Ag, respectively.…”
Section: Resultsmentioning
confidence: 78%